Persepsi Guru dan Siswa terhadap Penerapan Model Discovery secara Daring pada Pembelajaran Menulis Naskah Ceramah - Abdul Rahman; Yusak Hudiyono; Bibit Suhatmady (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
Implementation of online learning with the application of the invention model increases perceptions between teachers and students. This study aims to determine the perceptions of teachers and students about the implementation of the invention model online in writing script learning. The research method used is a qualitative method using a case study approach. The population in this study were Indonesian language subject teachers and ten-grade students. The sample was taken using the purposive sampling technique. Data collection techniques are carried out by filling out a questionnaire through the Google form and interviews with teachers and students.